Response of Andong Bamboo (Gigantochloa pseudoarundinacea) to Isocyanate Adhesive - Ignasia M Sulastiningsih; Surdiding Ruhendi; Muhammad Y Massijaya; Wayan Darnawan; Adi Santoso (Masyarakat Peneliti Kayu Indonesia, 2013)
The response of Gigantochloa pseudoarundinacea to isocyanate adhesive was investigated by evaluating its bonding quality. The bamboo strips were categorized based on the position at the bamboo culm viz bottom,midle, and top. One part of the bamboo strips were immersed in 7% boron solution for 2 hours.The treated and untreated bamboo strips were glued parallel to each other using the isocyanate adhesive at the glue spread of 250 g m-2 to produce two-ply laminates. The bonding surfaces of two-ply laminates were designed into 3 different combinations viz between inner and outer surfaces, both between inner surfaces, and both between outer surfaces. The bonding strength and bamboo failure were evaluated in dry and wet conditions. Results showed that the response of G. pseudoarundinacea to isocyanate adhesive was significantly affected by the posision at the bamboo culm, bamboo strips treatment and combination of bonding surfaces. In comparasion with the middle and the top part, the bottom part of bamboo culm had the highest bonding strength (dry test). However, the wet test results showed that the bonding strength of laminates made from bottom part did not significantly different with that of middle part. The preservation treatment on bamboo strips reduced the bonding strength.Key words: bamboo, bonding strength, isocyanate, laminates, preservation